Effects of Sesamol on Experimental CisplatinNephrotoxicity Model - Dilek, Mehmet Emin; Gurel, Alı; Doğantekin, Akif; Şahin, Kazım; Özercan, İbrahim Hanifi; İlhan, Necip; Çeliker, Hüseyin (My University, 2020)
Aim: Cisplatin causes oxidative damage in the kidney. Sesamol is one of the water-soluble and antioxidant compounds of sesame oil. We investigated the effect of sesamol on experimental cisplatin nephrotoxicity and lipid peroxidation.Material and Method: Twenty-eight male Wistar rats were used in 4 groups (n=7): control, sesamol (8 mg/kg/day), cisplatin (7 mg/kg i.p., single dose), and cisplatin + sesamol. Specimens were evaluated with biochemical, molecular and histopathologic methods. SPSS package programme was used for statistical analyses.Results: Urea and creatinine levels were significantly higher in the cisplatin group compared to the control group and were significantly decreased in the cisplatin+sesamol group (p<0.05). Cisplatin-treated rats showed a significant increase in malondialdehyde (MDA) levels (p<0.05). Sesamol significantly decreased MDA (p<0.05). Nuclear factor kappa B (NF-?B) levels increased in the cisplatin group compared to the control group and decreased significantly in the cisplatin+sesamol group (p<0.001). Nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) levels were decreased in the cisplatin group compared to the control group (p<0.001) and increased significantly in the cisplatin+sesamol group (p<0.01). Histopathological changes with cisplatin decreased with sesamol.Conclusion: We determined that sesamol decreases lipid peroxidation and NF-?B levels and shows antioxidant effect by increasing Nrf2 and HO-1 levels on cisplatin induced nephropathy
Keywords: Genel ve Dahili Tıp; Patoloji; Biyokimya ve Moleküler Biyoloji